Method of Buildings Structural Vulnerability and Geometry Form Designs Evaluation Towards Earthquakes With The SVA Architectural Design - Livian Teddy; Gagoek Hardiman; N. Nuroji; Sri Tudjono (Journal of Architectural Design and Urbanism, 2020)
In the process of architectural design, there is no special method employed by architects to evaluate buildings’ structural vulnerability and building geometry form designs towards earthquakes. Therefore, the alternative is adapting the existing method called SVA-Retrofit. JBDPA and Matsutaro Seki developed this method, and then the author adapted this method now called SVA Architectural Design. In the process of adaptation, deep literature review was conducted in order to acquire the adaptation results of the SVA-Architectural Design. These results can furthermore be an early prediction of structural vulnerability toward earthquakes that eventually leads to finding solutions for building designs or conducting detailed analysis done by structure experts.